2021
DOI: 10.2174/1385272824999201210180732
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in C–H Activation and Functionalization of Quinazolinones/ Quinazolines

Abstract: Abstract:: This review summarizes the transition metal-catalyzed direct C–H functionalization of quinazolinones and quinazolines through C-C, C-N and C-O bond formations. It focuses mainly on the C-H (sp2 or sp3) bond arylation, amination, sulfamidation, acetoxylation, halogenation, annulation of quinazolinones and quinazolines. This review illustrates the scope of C-H activation and functionalization of various quinazolinone and quinazoline derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 122 publications
0
5
0
Order By: Relevance
“…Subsequently, the reaction efficiency was examined in a THF mixture with other organic solvents (2 : 1). Product 4aaa could also be obtained in 76-92% yields in THF/acetone, THF/CH 2 Cl 2 , THF/CH 3 CN, and THF/ toluene (Table 1, entries [5][6][7][8]. Only a trace amount of the product was detected in a mixture of THF/DMSO (entry 9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the reaction efficiency was examined in a THF mixture with other organic solvents (2 : 1). Product 4aaa could also be obtained in 76-92% yields in THF/acetone, THF/CH 2 Cl 2 , THF/CH 3 CN, and THF/ toluene (Table 1, entries [5][6][7][8]. Only a trace amount of the product was detected in a mixture of THF/DMSO (entry 9).…”
Section: Resultsmentioning
confidence: 99%
“…4,5 Consequently, a number of methods have been developed for the construction of multi-substituted quinazolines via the latestage functionalization strategies. 6,7 On the other hand, in the past decades, visible-light-catalysis as a mild and powerful protocol has been widely utilized by the synthetic community to construct various important organic molecules. 8,9 In this context, light-driven carbene transfer reactions of α-diazo compounds have attracted great interest from chemists due to their metal-free and eco-friendly advantages, as well as versatile synthetic applications.…”
Section: Introductionmentioning
confidence: 99%
“…The classical method for the synthesis of quinazolinones involves the condensation reaction between 2-aminobenzamide and aldehyde in the presence of various catalysts [17,18], including acids [19,20] and metal catalysts [21]. However, such reactions commonly require toxic solvents [22,23] or high temperature [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Zhang et al [30] reported the synthesis of dihydroquinazolinone derivatives by efficiently catalyzing the condensation reactions of 2-aminobenzamide and a range of aldehydes with α-Chymotrypsin (Scheme 1, a). Compared to the traditional methods [19,21,26], this method had several advantages including its efficiency, high yield, and purity of the obtained products. Photocatalytic reactions are also green and safe [31,32] and have been successfully applied for the synthesis of quinazolinone heterocyclic compounds [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…5 Much attention has been paid to develop methods for the construction of quinazolinone derivatives in part to meet the growing needs for screening drugs. 6,7 The synthesis of organoselenium compounds has long been a fertile research field of laboratories and industries because of their wide biological applicability. 8 For example, organoselenylated heterocyclic molecules, such as compounds IV− VI, display many pharmaceutical activities (Figure 1b).…”
mentioning
confidence: 99%